Genetically modified plants in phytoremediation of heavy metal and metalloid soil and sediment pollution - Kotrba, Pavel; Najmanova, Jitka; Macek, Tomas; Ruml, Tomas; Mackova, Martina (Biotechnology advances, 2009)
Phytoremediation to clean up metal- and metalloid-contaminated soil or sediments has gained increasing attention as environmental friendly and cost effective. Achievements of the last decade suggest that genetic engineering of plants can be instrumental in improving phytoremediation. Transgenic approaches successfully employed to promote phytoextraction of metals (mainly Cd, Pb, Cu) and metalloids (As, Se) from soil by their accumulation in the aboveground biomass involved mainly implementation of metal transporters, improved production of enzymes of sulphur metabolism and production of metal-detoxifying chelators - metallothioneins and phytochelatins. Plants producing bacterial mercuric reductase and organomercurial lyase can covert the toxic ion or organomercury to metallic Hg volatized from the leaf surface. Phytovolatization of selenium compounds was promoted in plants overexpressing genes encoding enzymes involved in production of gas methylselenide species. This paper provides a broad overview of the evidence supporting suitability and prospects of transgenic research in phytoremediation of heavy metals and metalloids.
Keywords: geologické sedimenty; biodegradace; rostlinné geny; Biodegradation, Environmental; Genes, Plant; Metals, Heavy; Soil Pollutants; látky znečišťující půdu; Geologic Sediments; Biomass; geneticky modifikované rostliny; Plants, Genetically Modified; těžké kovy; biomasa